Academic Constructive Controversy and Conventional Learning: Moderating Effects of Achievement Motivation on Social Studies Outcomes - Aneka Trisma; Sumanti Sumanti; Siti Aisyah (Journal of Education Research, 2026)
Improving the quality of social studies learning at the elementary level requires innovative instructional strategies that accommodate diverse learner characteristics, including achievement motivation. This study aimed to examine the differential effects of Academic Constructive Controversy (ACC) and conventional learning on social studies outcomes among elementary students with varying levels of achievement motivation. A quasi-experimental design with a non-equivalent pretest-posttest control group was employed, involving 28 students from SD 122/III Mukai Tengah as the experimental class and 27 students from SD 169/III Mukai Mudik as the control class. Data were collected using an achievement motivation questionnaire and a social studies achievement test, then analyzed through two-way analysis of variance (ANOVA) with a 2×2 factorial design. The results indicated that ACC produced significantly higher social studies outcomes than conventional learning, and that achievement motivation level moderated this effect. Students with high achievement motivation benefited substantially from ACC, whereas those with low motivation showed more modest gains. These findings underscore the importance of aligning instructional methods with student motivational profiles to optimize learning outcomes.